2023
DOI: 10.1002/fsn3.3409
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of omega‐3 fatty acids on health outcomes in women with breast cancer: A systematic review

Shirin Osouli‐Tabrizi,
Amir Mehdizadeh,
Mina Naghdi
et al.

Abstract: This study aimed to systematically evaluate the impact of omega‐3 fatty acids on the health outcomes of women with breast cancer in electronic databases (PubMed, Scopus, ProQuest, Web of Science, and Cochrane Library) for interventional studies. The risk of bias and the quality of the included articles were assessed by Cochrane Collaboration Handbook guidance. The statistical analyses were not conducted because of the heterogeneity of the included studies. Of 3676 identified articles, 11 articles were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Several studies have confirmed the benefits of utilizing omega-3 PUFAs in cancer prevention, while the same was not observed for omega-6 PUFAs [ 34 ]. Omega-3 PUFAs have antioxidant and anti-inflammatory properties [ 35 , 36 ], contributing to the reduction in cytokine production, cell proliferation, and, consequently, tumor growth, leading to an apoptosis of tumor cells [ 37 ]. Another remarkable component of the prevention and treatment of BC is physical exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed the benefits of utilizing omega-3 PUFAs in cancer prevention, while the same was not observed for omega-6 PUFAs [ 34 ]. Omega-3 PUFAs have antioxidant and anti-inflammatory properties [ 35 , 36 ], contributing to the reduction in cytokine production, cell proliferation, and, consequently, tumor growth, leading to an apoptosis of tumor cells [ 37 ]. Another remarkable component of the prevention and treatment of BC is physical exercise.…”
Section: Introductionmentioning
confidence: 99%